11x-6=-39

Simple and best practice solution for 11x-6=-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-6=-39 equation:


Simplifying
11x + -6 = -39

Reorder the terms:
-6 + 11x = -39

Solving
-6 + 11x = -39

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 11x = -39 + 6

Combine like terms: -6 + 6 = 0
0 + 11x = -39 + 6
11x = -39 + 6

Combine like terms: -39 + 6 = -33
11x = -33

Divide each side by '11'.
x = -3

Simplifying
x = -3

See similar equations:

| 15=m-4m | | p-5-3=-9 | | 3x-7+x=10 | | -12=-5b-b | | 2(x+1)-4=5x-3(2+x) | | 7x-114=40-4x | | 9x-5x+3x-x+16=22 | | 42=28-12x | | (x^2)+6=8x | | -63-4x=135+7x | | 8=4-3b+1 | | 500+35*X=55*x | | -4n+2(-7n-5)=-7n+1 | | y^2=-4x^2+8x-3 | | X+36x=130 | | (x^2)-6x=1 | | -39-6b=-5(b+8) | | (4w^2)+12w+9=49 | | 3x=11x+25 | | -9cosx-3sinx=0 | | -9(k-1)=6-5(3k+3) | | 6(-4n-8)=96 | | -3n-5=-23 | | 8v+5=11 | | -4(-6b-4)=208 | | 7(7-12n)=-12n-11(n-10) | | 19(8c-1)-8=150c+19 | | 5x+8=7+3m | | 2+6a=-4+7a | | .06(x-.5)=.06x+0.01 | | -5(n+5)=2(8n-2) | | 1.2+6=9.6 |

Equations solver categories